Kesalahan Peserta Didik Menyelesaikan Soal Cerita Pada Materi Matriks Berdasarkan Kriteria Watson - Mulia Suryani; Lucky Heriyanti Jufri; Firdaus (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
This study aimed to describe the errors made by students in working on math story problems on the subject of the matrix based on Watson's error criteria. This type of research was descriptive research with quantitative methods. This study's data collection techniques used the method of tests, interviews, and documentation, while the subjects in this study were 35 people. The test was carried out only once with many questions of 4 story questions. Then the data obtained were analyzed by data triangulation techniques. This study indicated that most errors made by students were incorrect data errors (inappropriate data / ID) with an error percentage of 20.39%. In comparison, the minor errors made by students were omitted data (OD) errors with an error percentage of 2.63%. For the omitted conclusion (OC) error, response level conflict (RLC), indirect manipulation (UM), skill hierarchy problem (SHP), and in addition to the seven errors (others/ O) with an error percentage range of 10%â‰¤ P<25% and for inappropriate procedure errors (IP) with an error percentage range of P <10%. The causes of errors were lack of accuracy in reading and solving problems, errors in performing calculations, errors in using formulas, and lack of understanding of the material.